(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Rates have been increasing in cesarean deliveries over recent decades, which brings maternal morbidities. Objective: The objective of this article is to evaluate outcomes related to the quality of life after a caesarean. Methods: A cross-sectional study of pregnant women who underwent caesarean section was conducted, encompassing 102 cases over the course of one year (2023-2024). The outcomes of pregnancy and caesarean section for women aged 20–40 years were recorded. Additionally, a general questionnaire was administered to assess the quality of life of pregnant women patients after caesarean section. Findings: The data of 102 pregnant women who underwent caesarean delivery were enrolled. The data revealed that 64.71% of multiparous women and 26.47% of women who had previously experienced miscarriages underwent the procedure. The mean operation time was 57.23 ± 21.64 minutes, with a mean blood loss of 446.30 ± 392.84 millilitres. The mean hospital stay was 9.28 ± 7.72 days. There were nine cases of maternal mortality and 24 cases of surgical site adhesions. Pregnancy complications were identified in 31.37% of the total number of women. There were 12 cases of infant mortality. The questionnaire on quality of life revealed unfavourable outcomes with regard to general health, as evidenced by the Physical score of 45.7 ± 24.1, the role emotional score of 42.7 ± 20.6, the vitality score of 56.2 ± 17.2, and the bodily pain score of 66.7 ± 18.4. Summary: The findings of this study indicate that caesarean section has a detrimental impact on the quality of life of primiparous women.